Development economics - Ray, Debraj (Princeton, N.J. : Princeton University Press, 1998)
The book takes the position that there is no single cause for economic progress, but that a combination of factors - among them the improvement of physical and human capital, the reduction of inequality, and institutions that enable the background flow of information essential to market performance - consistently favor development.
Includes bibliographical references (p. [805]-828) and indexes.
oif 24/04/15
Loans
Keywords: Development economics; Economic development